Effects of Phosphorus Solubilizing Biofertilizers on Plant Growth and Seed Yield in Seed Parent of Sunflower (Helianthus annuus L.) Hybrid KBSH-44 - H.P. VIJAYAKUMAR; B.C. CHANNAKESHAVA; K. VISHWANATH; S. RAJENDRA PRASAD; SOMASUNDARAM G; K.R. SREERAMULU (Seed Research, 2026)
One of the major causes for low productivity of sunflower is poor seed setting which is due to insufficient nutrient (phosphorus) supply to the sink. Dual inoculation of phosphorus solubilizing biofertilizers, i.e. either B. megasterium or P. striata with G. fasiculatum, 60 or 90 days from sowing (DFS), significantly increased plant growth characters, viz. plant height, number of leaves, leaf area, stem girth, early flowering and decreased the days to maturity as compared to either uninoculated control or single inoculation. Likewise, significantly higher seed yield, viz. higher head diameter, seed filling % were recorded. A significant increase of raw seed yield (21.25%), seed recovery (%) and processed seed yield (20.67%) were also recorded in dual inoculations. Application of 100% recommended doses of phosphorus fertilizer (RDPF) showed significantly higher yield and yield attributes as compared to 50% RDPF.